100 años de la visita del Dr. Hideyo Noguchi al Perú y su contribución al estudio de la Enfermedad de Carrión - Shimabuku, Roberto (2020)
Little is known about the visit to Peru in april 1920, 100 years ago, of Dr. Hideyo Noguchi and his contribution to the study of Carrion’s disease or human bartonellosis. Perhaps because it is an almost exclusive disease in Peru, although cases have been reported in smaller numbers in Ecuador and Colombia, they have not had much international impact. Even though his visit was much commented by the newspapers of those years, time has blurred the activities of the visit, whose objective was to fight an outbreak of yellow fever in Paita. He spent three weeks in Piura and one week in Lima. It is in Lima that he learned of Carrion’s disease and the controversy as to whether La Oroya fever and peruvian wart were two distinct diseases or diferent phases of one disease. After five years he carried out numerous experimental investigations in New York contributing to the resolution of the controversy.